Digitalisasi Fidusia dan Kenotariatan: Solusi Hukum Modern di Era Cyber: DIGITALISASI FIDUSIA DAN KENOTARIATAN: SOLUSI HUKUM MODERN DI ERA CYBER - Riska, Apriani; Sesung, Rusdianto (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
Digitalization of fiduciary and notary is a strategic step in modernizing the legal system to answer the need for efficiency and transparency in the digital era. This research is motivated by the slow process of fiduciary registration and manual document attestation which is often considered inefficient and not in accordance with the demands of modern technology. This research aims to identify impacts, challenges, and solutions in the implementation of digital systems, including electronic signatures and blockchain, to support fiduciary and notary transformation. With qualitative methods, this research involves literature studies, interviews with 25 legal practitioners, and analysis of the application of digital technology in developed countries such as Estonia and Singapore. The results show that digitalization can cut the time for fiduciary registration from five working days to less than 24 hours, as well as increase transparency through real-time tracking. However, challenges in the form of technological resistance, infrastructure limitations, and data security issues remain obstacles. Blockchain is considered a potential solution for maintaining document integrity, but it requires large investments and strong regulation. In conclusion, the digitization of fiduciary and notary has great potential to improve efficiency, transparency, and security. The success of this transformation depends on the equitable distribution of infrastructure, education, and harmonization of regulations to ensure the legal validity of digital documents in the cyber era.